Comparison of frozen-thawed embryo transfer strategies for the treatment of infertility in young women: a retrospective study - Wu,Yanhong; Lu,Xiaosheng; Fu,Yanghua; Zhao,Junzhao; Ma,Liangliang (PeerJ, 2022)
Objective To investigate transfer strategies in the frozen-thawed embryo transfer (FET) cycle. Methods The clinical data of 1,652 FET patients were divided into five groups according to the number and quality of the transferred blastocyst: high-quality single blastocyst group (group A, n = 558), high-quality plus poor-quality double blastocyst group (group B, n = 435), poor-quality double blastocyst group (group C, n = 241), high-quality double blastocyst group (group D, n = 298), and poor-quality single blastocyst group (group E, n = 120). Inter-group comparison analyses of primary conditions, pregnancy outcomes and neonatal outcomes were then performed. Results Group A had the highest embryo implantation rate (67.38%), significantly different from the implantation rates of the other four groups. The gemellary pregnancy rate (1.60%), preterm birth rate (5.58%), neonatal birth weight (3,350g [3,000g, 3,650g]), neonatal birth age (39.57 weeks [38.71, 40.34]), and incidence of low birth weight (7.02%) in group A were different from those in groups B, C, and D, but did not significantly differ from those in group E. Moreover, the proportions of male infants born in groups A (56.86%) and D (59.41%) were significantly higher than those in the other three groups. Double blastocyst transfer (0.528, 95% CI [0.410–0.680], P < 0.001) and high-quality blastocyst transfer (0.609, 95% CI [0.453–0.820], P = 0.001) were found to be protective factors for live birth. In addition, double blastocyst transfer was also the largest risk factor for pregnancy complications (3.120, 95% CI [2.323–4.190], P < 0.001) and neonatal complications (2.230, 95% CI [1.515–3.280], P < 0.001), especially for gemellary pregnancy (59.933, 95% CI [27.298–131.58], P < 0.001) and preterm birth (3.840, 95% CI [2.272–6.489], P < 0.001). Based on the ROC curves, a double blastocyst transfer could predict gemellary pregnancy reliably with a high area under the curve (AUC = 78.53%). Additionally, a double blastocyst transfer could effectively predict a high risk of pregnancy complications (AUC = 65.90%), neonatal complications (AUC = 64.80%) and preterm birth (AUC = 66.20%). Conclusion The live birth rate of frozen-thawed high-quality single blastocyst transfer is lower than that of double high-quality blastocyst transfer, which can significantly increase the embryo implantation rate. High-quality single blastocyst transfer also significantly lowers the risk of gemellary pregnancy, preterm birth, and low birth weight, and can significantly improve maternal and infant outcomes. After weighing the pros and cons of live birth with pregnancy and neonatal complications, the authors believe that high-quality single blastocyst transfer is the optimal FET strategy for young women and is worthy of further clinical application. Despite this recommendation, high-quality single blastocyst transfer can increase the risk of monozygotic twins, as well as significantly increase the proportion of male infants born.
Keywords: Assisted reproductive technology; Frozen-thawed embryo transfer; Single blastocyst transfer; Gemellary pregnancy